Aplikasi Parameter Waktu Kontrol PID pada Heat Exchanger dengan Menggunakan Response Surface Methodology (RSM) - Muhammad Ikhsan Nst; Azhari Azhari; Nasrul ZA (Jurnal Teknologi Kimia Unimal, 2019)
Heat exchangers are tools used to transferring or transfer heat energy between a solid surface and fluid or inside different particles and in thermal contact. The objective of the study was to determine the optimum values of Kc, Ti and the best Td which to Heat exchangers of factory phenol design. Proportional-Integral-Derivative (PID) is a controller to determine the precision of an instrumentation system with the characteristics of feedback on the system. As the methodology of this research is to create a steady state Heat Exchanger model, then change the steady state model into a dynamic model, so create a PID model control, then tuning the PID control and testing PID controls, by disturbing the set point setting the valid point 115 ℃. The result of applying PID control system then got the fastest average time with value Kc = 8,82, Ti = 2,58, Td = 0 that is 0,38 minutes. At a temperature of 147.6 air vapor rate of 290.8 Kg / hr; at a temperature of 148.6 foundKeywords:heat exchanger, PID, set point, set point